Penyalahgunaan Kewenangan Oleh Aparat Desa Ditinjau Dari Aspek Pidana: (Putusan Pn Gorontalo Nomor 1/Pid.Sus-Tpk/2020/Pn Gto) - Sri Winda Latif; Lisnawaty w Badu; Ahmad Ahmad (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research is intended to: (1) find out how the review of the imposition of criminal sanctions for abuse of authority by village officials is based on the Gorontalo District Court Decision Number 1/Pid.Sus TPK/2020/PN Gto, and (2) find out what factors influence the imposition of crimes on Gorontalo District Court Decision Number 1/Pid.Sus-TPK/2020/PN Gto. This research uses a type of normative legal research that uses legal norms, including statutory regulations, doctrine, and judge's decisions as a foundation for providing arguments. The approach models used are the statutory approach, case approach and conceptual approach. The research results show: first decision no. 1/Pid.Sus TPK/2020/PN Gto, is not completely correct because prison sentences tend to be low and do not comply with legal principles and harm the sense of justice in society. Apart from that, the implications of the judge's decision in decision no. 1/Pid.Sus TPK/2020/PN Gto, if examined from the perspective of the principles of justice, expediency and legal certainty, these principles have not been fully implemented because it can be seen from the low number of judges' sentences against defendants. Second, the factors influencing the imposition of criminal sanctions in case no. 1/Pid.Sus TPK/2020/PN Gto, it was the absence of aggravating reasons applied by the panel of judges, and the public's perception or opinion of the defendant not being considered, which resulted in the sanction imposed being only 3 (three) years in prison.